Project-Based Sukuk (PBS) for Educational Infrastructure: Auction Mechanism and Procurement Governance at UIN Sayyid Ali Rahmatullah - Nur Rofik, Eka; Isno, Isno (El-kahfi | Jurnal Ekonomi Islam, 2025)
This study examines the governance of infrastructure development funded by State Sharia Securities (SBSN) at UIN Sayyid Ali Rahmatullah Tulungagung through Project-Based Sukuk (PBS). Using a qualitative case study approach, data were collected through interviews, field observations, and documentation analysis involving key stakeholders such as PPK, procurement officials, SPI, and project supervisors from the Ministry of Religious Affairs. The results indicate that SBSN financing strengthens transparency, accountability, and sharia compliance through digital procurement (LPSE), multilevel supervision, and asset-based financing using ijarah contracts. Infrastructure financed by PBS has significantly improved educational services, digital facilities, and institutional competitiveness, while also demonstrating social resilience during the COVID-19 pandemic. However, challenges persist in administrative complexity, centralized procurement, and capacity readiness, which may influence efficiency in project implementation. This research highlights that PBS is not only a financing instrument but also an accountability-driven governance model that aligns with Islamic public finance principles to support sustainable development in higher education.